ALGORITMA DETEKSI SUDUT AZIMUT DAN ELEVASI ROKET MENGGUNAKAN SEMBILAN ANTENA ARRAY YAGI-UDA - Satria Gunawan Zain; Adhi Susanto; Thomas Sri Widodo; Wahyu Widada (Jurnal Teknologi Dirgantara, 2011)
Radiation pattern of Yagi-Uda antenna is elliptical. This pattern can be used as a detector for the direction of the source of a radio emission. A total of nine Yagi-Uda antennas fitted with a 3x3 configuration. With this configuration, the measurement range for azimuth and elevation angles can reach 80º. The simulation was performed by using an antenna radiation pattern data. The number of antennas used for this simulation is nine. Then the data is merged into a 3x3 antenna configuration data. Based on data from nine antenna radiation patterns, the algorithm for the estimation of azimuth and elevation angles can be applied. Simulation results show that the measurement error of the signal without noise is close to zero. The algorithm used in this simulation can be applied to noise below 25%. Key word:Angle Estimation, Noise effects, Yagi-Uda Antennas, Rocket movement estimation